Harmonic Response of Human Subject in Sitting Posture Using FEM Analysis - Rohit Kumar, Sachin Kalsi, Ishbir Singh (International Journal of Advanced Science and Technology, 2020)
Human body exposed to vibration for make their work easy and comfortable that causes various types of various types of health problems due to the vibration effect on the human subject. Seat to head transmissibility as harmonic analysis has been performed on the 54 kg ellipsoidal shape human subject in the vertical sitting posture at excitation acceleration 1 m/s2 between frequency range 0-20 Hz with different damping conditions 0.2, 0.3 and 0.5. The solid model of the human subject has been designed by considering 50th percentile anthropometric data of Indian male subject. By performing harmonic response on the human subject it has been found that, at frequency 6 Hz the maximum effect of vibration has been occurred with the entire damping ratio. And also it has been observed that due to increasing of the damping ratio the effect of vibration has been decreases. The effect of the vibration has been occurred at various body parts like back, head, lower arm, etc. but the maximum effect has been found at head due to which the human feel sickness like headache, motion sickness, etc. during the traveling on the automotive. So it has been conclude that during the design of the seat in the transportation for the human comfort then the good quality seat cushion has to be used in more quantity.